Lao PDR acelerating structural transformation for inclusive growth country diagnostic study. (Metro Manila, Philippines Asian Development Bank, 2017)
This country diagnostic study provides comprehensive analysis and identifies promising new drivers of growth which the Lao PDR can develop to diversify its production.
Keywords: Sustainable development -- Lao People's Democratic Republic; Electronic books